The Effect of Task Based Language Teaching and Grammar Mastery on The Writing Competency of The Third Semester Students of English Education Study Program UNMAS Denpasar - Bawantara, I Putu Yoga (Universitas Halu Oleo, 2021)
This study was an experimental study aimed at finding out the effect of task-based language teaching and students‟ English grammar mastery on the students‟ writing competency. Post-test was administered to the experimental and control groups to obtain the result of students‟ writing competency after treatment was done with 2 x 2 factorial design. The population of study was the third semester students of English Education Study Program of UNMAS Denpasar consisted of 135 students where 52 students were chosen as the sample through intact group random sampling technique. The data of the research were collected through a grammar mastery test and writing test and were analyzed by using Two-Way ANOVA and Tukey-test assisted by SPSS 22.0. The research findings showed: (1) The students who were treated by using task-based language teaching got better score in writing competency than those who were treated by using common teaching strategy (2) There was no interactional effect between task-based language teaching and grammar mastery over the students‟ writing competency where the findings showed the null hypotesis H0 was accepted. It means, there was no interaction between task-based language teaching strategy and students‟ grammar mastery upon students‟ writing competency. Where the data output showed the probability value was 0.758, which was higher than 0.05. (3) There was no any significant difference in writing competency between the students who have high grammar mastery taught by using Task-based Language Teaching and those who are taught by common teaching strategy. The finding of the significant value was more than 0.05 which was 0.113. To be called significant, the 2-tailed (sig.) scores should below 0.05. Because the (sig.) score was above 0.05, there differences between these 2 group can be called as not significantly different. (4) There was a significant difference in writing competency of the students who have low grammar mastery between those who were taught by using Task-based Language Teaching and those who were taught by using common learning strategy. It coud be seen from the result of the data computation that 2-tailed (sig.) score was 0.02. which was below 0.05. Therefore, it can be said that the differences between control group and experimental group was significant. It can be concluded that Task-based Language Teaching, had given better result to students‟ writing competency. Even though, it could give significant or insignificant interaction to students who had high and low English grammar mastery. Descriptively and inferentially, students who were taught by using TBLT performed better than students who were taught by using common teaching strategy.